Association between human herpes simplex virus and severe headache or migraine among aged 20–49 years: a cross-sectional study - Zheng, Tao; Jiang, Li; Li, Guanglu; Zeng, Na; Yu, Binyang; Duan, Shaojie; Wang, Gesheng; Liu, Zunjing (Frontiers in Neurology, 2024)
infection may be associated with the onset of headache or migraine. We aimed to investigate the association between HSV infection and severe headache or migraine.The cross-sectional data on 5,730 participants aged 20-49 years were obtained from the 1999-2004 National Health and Nutrition Examination Survey (NHANES). We used weighted logistic regression analysis to assess the association between HSV infection (HSV-1 gG-1 and HSV-2 gG-2) and severe headache or migraine, and performed subgroup analyses.Results: Our study found that women, higher education, higher body mass index, better family conditions, smoking and alcohol consumption were all associated with severe headaches or migraines. After adjusting for confounding factors such as sex, age, race, and education, HSV-2 (+) was still significantly associated with severe headache or migraine (OR = 1.22, 95%CI:1.03-1.46, P = 0.0443). In subgroup analyses, we found that participants with HSV-1 (-) and HSV-2 (+) were also significantly associated with severe headache or migraine(OR = 1.41, 95%CI:1.04-1.91, P = 0.0281).Conclusions: HSV-2 gG-2(+) was significantly associated with severe headache or migraine.